Invertase from a Candida stellata strain isolated from grape: production and physico-chemical characterization - Gargel, Cristiane Abe [UNESP]; Baffi, Milla Alves; Gomes, Eleni [UNESP]; Silva, Roberto da [UNESP] (Slovak University of Agriculture in Nitra, 2014)
Invertases are enzymes which hydrolyze the sucrose and are widely employed in food and pharmaceutical industries. In this work, the screening of autochthonous grape yeasts from Brazil was carried out in order to investigate their invertase production potential. Yeasts belonging to Saccharomyces, Hanseniaspora, Sporidiobolus, Issatchenkia, Candida, Cryptococcus and Pichia genera were analyzed by submerged fermentation (SbmF) using sucrose as substrate. Among them, Candida stellata strain (N5 strain) was selected as the best producer (10.6 U/ml after 48 hours of SbmF). This invertase showed optimal activity at pH 3.0 and 55°C, demonstrating appropriate characters for application in several industrial processes, which includes high temperatures and acid pHs. In addition, this invertase extract presented tolerance to low concentrations of ethanol, suggesting that it could also be suitable for application at the beginning of alcoholic fermentation. These data provide promising prospects of the use of this new invertase in food and ethanol industry.
Keywords: Grape yeasts; non-Saccharomyces; invertase; food industry